Bulk growth of Neisseria gonorrhoeae type 1 in a biphasic system. Issue 6 (December 1978) - Ison, C; Glynn, A A
Abstract : A biphasic system for the bulk growth of Neisseria gonorrhoeae is described. It appears to combine the convenience of liquid media with the growth qualities of solid media. By using the agar in dialysis tubes rather than as slabs the surface-to-volume ratio was improved and harvesting made easier. The system is also useful in isolating gonococci from blood and joint fluids in patients with disseminated infection.